2021
DOI: 10.1017/s0950268821000789
|View full text |Cite
|
Sign up to set email alerts
|

Public health response to an outbreak of SARS-CoV2 infection in a Barcelona prison

Abstract: An outbreak of SARS-CoV2 infection in a Barcelona prison was studied. One hundred and forty-eight inmates and 36 prison staff were evaluated by rt-PCR, and 24.1% (40 prisoners, two health workers and four non-health workers) tested positive. In all, 94.8% of cases were asymptomatic. The inmates were isolated in prison module 4, which was converted into an emergency COVID unit. There were no deaths. Generalised screening and the isolation and evaluation of the people infected were key measures. Symptom-based su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…A total of 1250 articles did not meet the inclusion criteria. Therefore, 21 articles were included in the present systematic review ( Figure 1 ) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…A total of 1250 articles did not meet the inclusion criteria. Therefore, 21 articles were included in the present systematic review ( Figure 1 ) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…In prisons, when there is an ongoing outbreak, maintaining social distancing, even as necessary, can be physically impossible when cells are shared and dining rooms and spaces for daily sociocultural activities are common ( 12 , 20 – 22 ). Actions to reduce the prison population are crucial, such as delaying minor trials, advancing releases in prisoners with misdemeanors and, above all, providing for people at high risk of serious illness with alternative forms of custody such as community-based parole, if the jails and prisons do not guarantee inmate protection during this pandemic ( 20 , 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are different strategies for viral testing during an outbreak including universal testing, reactive testing, and prevalence testing ( 11 ). Similar to other conglomerate centers, testing of contacts even if asymptomatic is crucial to halt the spread of COVID-19 outbreaks ( 22 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Marco et al reported data on a SARS-CoV-2 outbreak in a Barcelona prison. Among 148 incarcerated people who underwent nasopharyngeal swab, 22.3% tested positive for SARS-CoV-2 ( 22 ). The available study findings have been reported in Table 1 .…”
Section: Sars-cov-2 Spread In Prison Settingsmentioning
confidence: 99%